Estudo da fibrose e esteatose hepáticas, em cirurgia bariátrica, por meio da elastografia transitória - Lima, Ramon Rawache Barbosa Moreira de (2022)
Nonalcoholic fatty liver diseaseis found in most patients with obesity and has a strong association with metabolic syndrome. The Roux-en-Y Gastric Bypass (BPGYR) and Vertical Gastrectomy (GV) are the two most used bariatric surgery techniques in the world. Patients who undergo bariatric surgery have regression of nonalcoholic steatohepatitis due to reduction in body mass index and changes in incretin hormones.The objective of this study is to analyze whether there is a difference in pre and postoperative measurements of liver steatosis and fibrosis in patients undergoing RYGB and GV two months after surgery. The patients in the preoperative period of bariatric surgery underwent an anthropometric evaluation and a hepatic elastography to quantify fibrosis and hepatic steatosis. Two months after surgery, the same evaluation was performed again. 18 patients met all the inclusion criteria for the study. Nine underwent VSG and 8 underwent RYGB. The RYGB group had lower levels of liver fibrosis postoperatively compared to preoperatively, but with p = 0.054, not showing statistical significance. As for steatosis, patients who underwent RYGB had lower postoperative steatosis in the postoperative period when compared to the preoperative period (p = 0.011). In the GV group, there was no statistical significance either in the comparison of pre- and postoperative steatosis (p=0.092) or in the comparison of pre- and postoperative fibrosis (p = 0.264). RYGB proved to be an adequate surgical method to improve hepatic steatosis in a 2-month postoperative period.